Determinant Of Incentive Factors In Knowledge Sharing (Study At Multimedia University) - Behjati, Saeed (2009)
The main focus on this research is based on social factors considering (predecessor phase) and Knowledge absorption (successor phase) abreast of its focus in knowledge dissemination.